2016
DOI: 10.14814/phy2.12765
|View full text |Cite
|
Sign up to set email alerts
|

TNF/Ang-II synergy is obligate for fibroinflammatory pathology, but not for changes in cardiorenal function

Abstract: Angiotensin‐II (Ang‐II) infusion is associated with the development of interstitial fibrosis in both heart and kidney as a result of chemokine‐dependent uptake of monocytes and subsequent development of myeloid fibroblasts. This study emphasizes on the synergistic role of tumor necrosis factor (TNF) on the time course of Ang‐II‐induced fibrosis and inflammation in heart and kidney. In wild‐type (WT) hearts, Ang‐II‐induced fibrosis peaked within 1 week of infusion and remained stable over a 6‐week period, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Prevalence of M1 and M2 was associated with a proinflammatory and profibrotic cytokine milieu, respectively, and evidence was reported that formation of M2 cells was dependent on production of TNF-␣ by M1 cells (247). However, the exact identity and function of the myeloid fibrocytes in ANG II-induced cardiac fibrosis is unclear given the previously discussed results of lineage tracing and the relative transient presence of the myeloid fibrocytes in the heart (672).…”
Section: Inflammation and Cardiac Fibrosismentioning
confidence: 99%
“…Prevalence of M1 and M2 was associated with a proinflammatory and profibrotic cytokine milieu, respectively, and evidence was reported that formation of M2 cells was dependent on production of TNF-␣ by M1 cells (247). However, the exact identity and function of the myeloid fibrocytes in ANG II-induced cardiac fibrosis is unclear given the previously discussed results of lineage tracing and the relative transient presence of the myeloid fibrocytes in the heart (672).…”
Section: Inflammation and Cardiac Fibrosismentioning
confidence: 99%
“…Similar data were obtained in another model of hypertrophic cardiomyopathy. In an angiotensin II osmotic minipump model, Tnfa −/− and Tnfrsf1a −/− mice showed significantly attenuated phenotype [ 126 , 127 ]. In-depth analysis demonstrated reduced immunofibrotic changes in the myocardium of Tnfrsf1a −/− mice, but there was no protective effect on diastolic dysfunction in this model [ 127 ].…”
Section: Tnf-α In Animal Models Of Cardiovascular Diseasesmentioning
confidence: 99%
“…In an angiotensin II osmotic minipump model, Tnfa −/− and Tnfrsf1a −/− mice showed significantly attenuated phenotype [ 126 , 127 ]. In-depth analysis demonstrated reduced immunofibrotic changes in the myocardium of Tnfrsf1a −/− mice, but there was no protective effect on diastolic dysfunction in this model [ 127 ]. In contrast, Tnfrsf1b −/− mice receiving angiotensin II infusion developed fibrosis and showed only slight changes in expression of pro-fibrotic genes [ 128 ].…”
Section: Tnf-α In Animal Models Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Although that study did not measure inflammatory biomarkers, aging is associated with the development of inflammatory states. Another study demonstrated that angiotensin‐II infusion in mice introduced a fibroinflammatory response that is followed by kidney tubulointerstitial collagen deposition mediated through the TNF‐R1 signaling pathway and speculated that TNF α ‐R1 triggers collagen deposition . A significant association between lipocalin 2 in mesangial cells and sTNF α ‐R2 levels and impaired kidney function has also been reported .…”
Section: Discussionmentioning
confidence: 97%